(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
A significant number of unnatural deaths of females occur in the age group of 15–45 years because this is the age when young girls or women have to go through the important changes of their lives such as education, marriage, job, family responsibility etc. A prospective cross-sectional study was carried out between 11 April 2012 to 10 April 2013 at mortuary, S.R.N. Hospital, Allahabad with the main aim of determining various epidemiological aspects, causes and manner of unnatural deaths of females in the age group of 15–45 years. Amongst 2857 autopsies performed during the study period, 864 (30.24%) victims were female. Amongst 864 female victims, 593 (68.63%) females were in the age group studied. The age group of 15–25 years included maximum number of deaths (54.13%) in study sample (n=593). Burns was the most common mode of death. Septicaemic shock was the most common cause of death (47.96%). Unnatural deaths were highest in Hindu females (78.07%) and higher in rural (71.84%) than in urban (28.16%) areas. Out of 467 married females, 241 (51.61%) died within 7 years of their marriage, most probably due to widely prevalent evil of ‘dowry death’ in India. Accident was the most common manner of death (46.37%). A comprehensive study was done revealing the need of various socio-cultural and legal measures to be taken to handle the grave results of this study.